Multiletramentos no ensino de língua inglesa: uma intervenção pedagógica na escola pública de ensino médio - Mendes, Eliziane de Sousa Sampaio (2020)
English language teaching has undergone significant modifications in order to meet the needs that arise with the advancement of technologies and globalization in recent years. In this research, aiming to approach the teaching of the Modern Foreign Language, we present a proposal for pedagogical intervention based on the theory of multiliteracies - which incorporate both multimodality and multiculturalism into its concept, present in the most diverse forms of social interactions - and learning by design (THE NEW LONDON GROUP, 1996; COPE; KALANTZIS, 2009). The teaching proposal is structured according to the learning processes of learning by design, contemplating the resolution of four activities performed by WhatsApp app, which acted both as a support for posting responses and as a means of interaction for participants. The proposal was developed in line with the skills and competences regulated in the National Common Curricular Base and directed to students of the first series of High School with low performance in the first two months of the academic year of 2019, in the aforementioned discipline. The evaluation of the intervention is established through the analysis of interactions made on WhatsApp, the resolution of activities and a questionnaire carried out with students at the end of the intervention. In view of the demands of the modern world regarding the practices of multiliteracies, we believe that the present research can contribute to an English language teaching that meets the social needs of communication and that enables students to use media resources according to critical and conscious learning